(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1855)
Communications regarding the opening of a National Exhibition of Portraits of Illustrious Scotsmen. Contains the letter from the Society to the Board of Trustees for Manufactures in Scotland and the reply indicating that the Society should contact the Royal Scottish Academy who were undertaking a project with similar aims. The Council agreed to do so and the session was adjourned on November 30th, 1854.